Discussion about math, puzzles, games and fun.   Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ • π ƒ -¹ ² ³ °

You are not logged in.

## Post a reply

Write your message and submit
|
Options

## Topic review (newest first)

bob bundy
2013-10-26 18:29:27

That's what I was assuming.

b + e = constant => a+ c is constant.

All you need to fill in is the arithmetic mean.  Do you know what that is?

Bob

mukesh
2013-10-26 03:50:10

sir here beginning and last numbers are constant,fixed.
plse explane in brief ,i m in trouble

bob bundy
2013-10-25 21:32:13

hi mukesh

I am not very clear about what is variable and what fixed here.  Let's see if I can sort this out.

Let beginning = b
end = e

first quantity = a
second quantity = c

equidistant => a - b  = e - c

=> a + c = e + b

So, if e and b are fixed it should be easy for you to finish this off.

Bob

mukesh
2013-10-25 20:32:18

show that the sum of the arithmetic means between two given quantities ,equidistant from the beginning and the end is constant.

## Board footer

Powered by FluxBB